Comparison of bacterial contamination and antibacterial efficacy in bristles of charcoal toothbrushes versus noncharcoal toothbrushes: A microbiological study - Mitali Vilas Thamke; Amol Beldar; Priya Thakkar; Supriya Murkute; Varsha Ranmare; Anuja Hudwekar (Wolters Kluwer Medknow Publications, 2018)
Background: Charcoal toothbrushes have been marketed widely claiming lesser bacterial contamination owing to the presence of activated charcoal. Aim and Objective: The aim of this study was to evaluate the bacterial contamination and antimicrobial efficacy of charcoal bristles compared to noncharcoal bristles in used toothbrushes. Materials and Methods: A total of 50 patients met inclusion criteria which were given standard brushing instructions on the use of a charcoal toothbrush and were asked to return the used brushes after 1 week of usage. After a washout period of 1-week, the participants were then provided with noncharcoal toothbrush and given similar brushing instructions to both groups and were instructed to return the brush after another week of usage. Bristles of the used toothbrushes were sectioned and placed in a 5 ml of saline, and 0.1 ml was inoculated on blood agar plates, which were then placed in a gas pack jar for anaerobic culture. Colony forming units (CFU) were measured after 48 h of incubation. To evaluate the antibacterial efficacy of charcoal bristles, the zone of inhibition was evaluated for charcoal versus noncharcoal after 24 h of incubation. Data collected were analyzed using a paired sample t-test. Results: The mean CFU count for noncharcoal bristles was almost double that of charcoal bristles. About 10 mm of the zone of inhibition was found around charcoal bristles as compared to 3 mm for noncharcoal bristles. Conclusion: This study shows the statistically significant difference in bacterial counts between bristle types and lower CFUs in the charcoal bristles compared with noncharcoal bristles, after 1 week of use. The zone of inhibition that was found around charcoal tooth bristles supported the antimicrobial properties of the charcoal toothbrush.